Who's holding the moral higher ground: Religiosity and the vertical conception of morality. (1st February 2017) - Li, Heng; Cao, Yu
Abstract: Across languages, "morality" is associated with "up" and "immorality" with "down". The relationship between morality and verticality found in linguistic metaphors can also be found in people's non-linguistic mental representations of morality. However, recent lines of work have demonstrated that personality differences may moderate the embodied effect of moral concepts on a vertical dimension. Based on these findings, we predicted that, by virtue of its facilitating role in encouraging moral thinking and behavior, religiosity may contribute to a stronger embodied effect of moral concepts. We found convergent support for this hypothesis across two studies using correlational (Study 1) and experimental data (Study 2). The findings suggest that there are individual differences in the metaphorical representation of moral concepts. Highlights: We studied the relationship between religiosity and vertical conception of morality. We found that religiosity may contribute to a stronger embodied effect of moral concepts. We suggest that there are individual differences in the metaphorical representation of moral concepts.